Assisted reproduction in endometriosis. Issue 1 (February 2019) - de Ziegler, Dominique; Pirtea, Paul; Carbonnel, Marie; Poulain, Marine; Cicinelli, Ettore; Bulletti, Carlo; Kostaras, Konstantinos; Kontopoulos, George; Keefe, David; Ayoubi, Jean Marc
Abstract : Endometriosis – a disease causing pain and infertility – is encountered in nearly 50% of infertile women. While medical treatment is effective on pain and recurrence of symptoms after surgical excision, it is of no help for treating infertility for which the only options considered are surgery and ART. Surgery enhances the chances of conceiving naturally during the 12–18 ensuing months irrespective of the stage of the disease. Surgery however is of no help when ART is considered, as it does not improve outcome and can only harm the ovarian response to stimulation. Today therefore, ART is commonly the primary option to be considered in women whose infertility is associated with endometriosis and whose ovarian reserve is compromised and/or who are over 35 years of age. When, ART is envisioned it is best to opt for a segmented ART approach with agonist trigger, freeze all and deferred embryo transfer.